TINJAUAN YURIDIS TERHADAP AKIBAT HUKUM WANPRESTASI DALAM PERJANJIAN HUTANG PIUTANG TANPA AKTA NOTARIS DI INDONESIA - Priyono, Edi; Astutik, Sri; Widodo, Ernu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the legal consequences of default in loan agreements made without notarial deeds in Indonesia, focusing on three key aspects: the legal standing of such agreements, implications of default, and dispute resolution mechanisms. The research addresses critical issues including legal uncertainty due to the absence of notarial authentication, evidentiary challenges in court proceedings, and the effectiveness of various dispute resolution approaches. The study employs a normative juridical method with statutory, conceptual, and case law approaches, analyzing provisions in the Indonesian Civil Code (particularly Articles 1238, 1243, 1320, and 1870), relevant court decisions, and legal doctrines from various scholarly works. The findings reveal that while loan agreements without notarial deeds remain valid under Article 1320 of the Civil Code provided they meet the four validity requirements, the lack of authentic documentation creates significant evidentiary complications. Default in such agreements entitles creditors to demand performance or compensation (Article 1243), but the burden of proof often relies on weaker evidence like witness testimony. Dispute resolution may proceed through either litigation in courts or alternative methods such as mediation and arbitration, though litigation tends to be more time-consuming and costly. This study recommends formalizing loan agreements through written notarial deeds to enhance legal certainty. Additionally, it suggests public legal education about the risks of informal agreements and regulatory improvements to better protect parties involved in non-notarized loan agreements